Prototyping of a Digital Life Course Care Platform for Preconception and Pregnancy Care: Pilot Feasibility and Acceptability Study - Melissa van der Windt; Sofie Karolina Maria van Zundert; Sam Schoenmakers; Lenie van Rossem; Régine Patricia Maria Steegers-Theunissen (JMIR Publications, 2023)
BackgroundA healthy lifestyle plays a key role in the prevention of lifestyle-related diseases, including subfertility and pregnancy complications. Although the benefits of a healthy lifestyle are well-known, long-term adherence is limited. Moreover, memory for lifestyle-related information as well as medical information provided by the medical professional is often poor and insufficient. In order to innovate and improve health care for both the patients and health care professionals, we developed a prototype of a digital life course care platform (Smarter Health app), providing personalized lifestyle care trajectories integrated in medical care journeys. ObjectiveThis pilot study aimed to evaluate the feasibility, defined as the actual app use, and the acceptability, which included patient satisfaction and appreciation, of the Smarter Health app. MethodsBetween March 17, 2021, and September 30, 2021, pregnant women familiar with the Dutch language seeking tertiary preconception and pregnancy care were offered the app as part of standard medical care at the outpatient clinic Healthy Pregnancy of the Department of Obstetrics and Gynecology of the Erasmus University Medical Center. Three months after activation of the app, patients received a digital questionnaire consisting of aspects of feasibility and acceptability. ResultsDuring this pilot study, 440 patients visited the outpatient clinic Healthy Pregnancy. Of the 440 patients, 293 (66.6%) activated the app. Of the 293 patients who activated the app, 125 (42.7%) filled out the questionnaire. Of these 125 patients, 48 (38.4%) used the app. Most app users used it occasionally and logged in 8 times during their medical care trajectory. Overall, app users were satisfied with the app (median 5-point Likert scale=2.4, IQR 2.0-3.3). ConclusionsOur findings showed that the Smarter Health app, which integrates lifestyle care in medical care, is a feasible health care innovation, and that patients were satisfied with the app. Follow-up and evaluation of pregnancy outcomes should be performed to further substantiate wider clinical implementation.